Cooperation and the in-group-out-group bias a field test on Israeli Kibbutz members and city residents - Ruffle, Bradley; Sosis, Richard (2003)
The in-group-out-group bias is among the most widely documented and analyzed phenomenon in the social sciences. We conduct field experiments to test whether the bias extends to the cooperative behavior of one of the most successful modern collectives, the Israeli kibbutz. Despite their promise as universal cooperators, kibbutz members are more cooperative toward anonymous kibbutz members than they are toward anonymous city residents. In fact, when paired with city residents, kibbutz members' observed levels of cooperation are identical to those of city residents. Moreover, self-selection rather than kibbutz socialization largely accounts for the extent to which kibbutz members are cooperative.